Steps in hypothesis testing (one mean) / Siti Balqis Mahlan - Mahlan, Siti Balqis (Unit Penerbitan JSKM, 2020)
We begin by stating the value of a population mean in a null hypothesis. For example, we state that the null hypothesis that students in Universiti Teknologi MARA Cawangan Pulau Pinang, Malaysia study with an average of 2 hours per day. We will test whether the value stated in the null hypothesis is likely to be true. Keep in mind that the only reason we are testing the null hypothesis is because we think it is wrong. We may have reason to believe that students study more than 2 hours or less than 2 hours per day. We also can state that the value in null hypothesis is not equal to 2 hours.